SATIRE NEWS AND GENERATION Z RECEPTION ON MEET NITE LIVE METRO TV - Utami, Sinta Dwi; Azis, Abdul (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study examines how satirical discourse is constructed in television news and how Generation Z interprets it, focusing on Meet Nite Live, a MetroTV program that combines journalism with comedy. The program adopts a casual yet sharp style, embedding socio-political critique within humorous conversations to capture younger audiences. Using Fairclough’s Critical Discourse Analysis and Stuart Hall’s Reception Analysis, this research examines the relationship between the satire production and audience interpretation. Data were collected through program text analysis and in-depth interviews with Generation Z respondents. Findings reveal that Meet Nite Live employs informal language and satire to present critique in a non-confrontational manner, making sensitive issues more accessible and relatable. All respondents occupy a negotiated position: they acknowledge the substance of the critique but critically assess its delivery and entertainment value. This confirms that Generation Z functions as an active and discerning audience. Moreover, platform and algorithmic gatekeeping significantly shape the program’s reach, as short-form content on YouTube Shorts and TikTok often serves as the entry point for young viewers. The study concludes that satire sustains media relevance, fosters critical literacy, and strengthens democratic engagement. Meet Nite Live exemplifies how mainstream media can adapt to digital logics while maintaining socio-political issues.